The difference maximum bite force and mastication ability in patients wearing metal framework and acrylic removable partial dentures: Perbedaan kekuatan gigit maksimal dan kemampuan mastikasi pasien pengguna gigi tiruan sebagian lepasan kerangka logam dengan akrilik - Hastinawaty; Nurimah Wahyuni; Ike Damayanti Habar; Eri Hendra Jubhari; Irfan Dammar (Makassar Dental Journal, 2025)
Dentures are expected to restore masticatory function, which is an indicator of the functional complex of mastication influenced by elevator muscle activation from craniomandibular biomechanics. The level of bite force is important to determine the effectiveness of mastication in denture-using patients. This study evaluated the differences in maximal bite force values and masticacation ability in metal and acrylic partial denture patients. Subjects were RPD users; 12 metal frame patients and 12 acrylic patients. The bite force values the patients were measured using a byte gauge. Mastication ability was assessed using a mastica-cation ability questionnaire. The age groups of 46-55 years and 56-65 years used the RPD the most. The mean maximal bite force of metal-frame RPD patients was 260.92 N and 90.67 N in acrylic. All of the metal frame users had good mastication ability and only 5% of acrylic RPD users had good ability. Only 66.7% of metal frame RPD patients had a high quality of life and 8.3% of acrylic. It was concluded that the maximal bite force value of metal frame RPD patients was greater than acrylic.